Analysis of Ict Learning In Increasing The Intellectual Intelligence of Students In MTSN 4 Aceh Utara - Viviani, Nora; Almuhajir, Almuhajir; Hasibuan, Zainuddin (Dinasti International Journal of Management Science, 2024)
Information and Communication Technology (ICT) education aims to provide knowledge and skills to learners in order for them to stay updated on technical advancements that are constantly changing. ICT learning at MTsN 4 Aceh Utara requires a variety of strategies and methods that emphasize the development of thinking, analysis, and problem-solving skills to enhance the intellectual intelligence of learners. The research is qualitative and uses methods of comparative analysis, involving students directly in the learning analysis of ICT. The results of the research show that intellectual intelligence has a positive influence in developing critical thinking, creativity, and analytical ability of students in MTsN 4 Aceh Utara. Average percentage results showed 73.3% for the learning material aspects of ICT, 70% for learning methods aspects, and 73,3% for learning evaluation aspects. These findings contributed to the overall improvement of learning quality in MTsN 4 Aceh Utara.